Growth, nodulation and yield responces of promiscuous and specific-nodulation soybean cultivars to rhizobium inoculation and seaweed extract - Raofa, Tshepo Prince (My University, 2021)
Soybean (Glycine max L.) is one of the valuable leguminous crops with grain used for human consumption, livestock feeding, bio-fuel (bio-diesel) production, vegetable oil and is a protein resource. The crop also fixes atmospheric nitrogen. The study aimed to evaluate the performance of two soybean varieties to a combination of inoculation and seaweed extract. The research trial was conducted at Syferkuil farm during 2017/2018 summer season in which two soybean varieties (TGx 1937-1F promiscuous) and (PAN 1583R specific-nodulating) were evaluated for their growth, nodulation and yield responses to rhizobium inoculation and seaweed extract (0 % rate (0ml/12L), 50 % rate (30ml/12L) and 100 % (60ml/12L). The research trial was laid out as a split-split plot arrangement fitted in RCBD with four replications. Inoculation significantly influenced grain yield at P≤0.05, seed nutrient content and total above-ground biomass, except for seed potassium. No inoculation significantly achieved higher primary branches per plant at P≤0.05, pod number per plant, stem diameter (P≤0.05), grain yield (P≤0.05), harvest index and total above-ground biomass at P≤0.001. The variety TGx 1937-1F had significantly (P≤0.001) higher nodule number per plant, effective nodules per plant, nodule dry weight, dried shoot biomass, leaf number per plant, pod number per plant, primary branches per plant, stem diameter, plant height, leaf chlorophyll content, total above-ground biomass, grain yield and seed iron (Fe) content. Application of full rate seaweed extract significantly (P≤0.001) increased primary branches per plant, stem diameter, leaf number per plant, plant height, shelling percentage, total above-ground biomass, grain yield, and seed content of calcium (Ca), potassium, magnesium (Mg), manganese (Mn) and sodium (Na) all at P≤0.05. Seaweed extract rate at 0 % obtained the highest harvest index (P≤0.001). Inoculation and variety TGx 1937-1F interaction exhibited a significant increase on leaf number per plant at P≤0.001, primary branches per plant at P≤0.001 and plant height at P≤0.001. Variety TGx 1937-1F, without inoculation, obtained significantly higher pod number per plant (P≤0.001), stem diameter at P≤0.001, grain yield at P≤0.05 and total above-ground biomass at P≤0.001. Variety PAN 1583R, without inoculation, obtained significantly higher harvest index and shelling percentage at P≤0.001. Interaction of vi inoculation and seaweed extract showed that no inoculation × 100 % rate of seaweed extract significantly (P≤0.001) increased primary branches per plant, leaf number per plant, stem diameter, pod number per plant and plant height. Interaction of inoculation × 100 % rate of seaweed extract increased grain yield (P≤0.001) and total above-ground biomass at P≤0.001. Inoculation × 50 % rate of seaweed extract interaction increased shelling percentage at P≤0.001. No inoculation × 0 % rate of seaweed extract interaction obtained significantly higher harvest index (P≤0.001). Interaction of variety and seaweed extract showed that variety TGx 1937-1F × 100 % rate of seaweed extract significantly increased primary branches per plant (P≤0.001), pod number per plant at P≤0.001, grain yield at P≤0.001 and total above-ground biomass at P≤0.001. The variety TGx 1937-1F × 50 % rate of seaweed extract significantly raised the size of stem diameter (P≤0.01) and plant height (P≤0.001). Three-way interactive effects of inoculation × variety TGx 1937-1F × 100 % rate of seaweed extract obtained significantly higher number of shelling percentage at P≤0.001, leaf number per plant at P≤0.05 and primary branches per plant at P≤0.001. Interaction of no inoculation × variety TGx 1937-1F × 100 % rate of seaweed extract obtained significantly high pod number per plant at P≤0.001, grain yield at P≤0.05, total above-ground biomass at P≤0.001 and plant height at P≤0.001. No inoculation × PAN 1583R × 100 % rate of seaweed extract interaction had a higher harvest index at P≤0.001. The study showed that inoculation, seaweed extract, or their combination generally enhanced seed nutrient content, especially in variety TGx 1937-1F. The study further showed that promiscuous soybean (TGx 1937-1F) had higher grain yield, under stressful growing conditions as compared to PAN 1583R variety. This implies that soybean variety TGx 1937-1F, with 50 % or 100 % application rate of seaweed extract could be recommended to smallholder farmers. Key words: Soybean, inoculation, seaweed extract, phenological development, growth, nodulation, grain yield and seed nutrient content.
Thesis (M.Sc. (Agronomy)) -- University of Limpopo, 2021
Keywords: Soybean; Inoculation; Seaweed extract; Phenological development; Growth; Grain yield and seed nutrient content; Nodulation; Cooking (Soybeans); Beans - Harvesting